MONITORING JARINGAN MENGGUNAKAN APLIKASI CACTI DI STMIK MURA LUBUKLINGGAU - Nelly Khairani Daulay (Jurnal Informatika dan Komputer (JIK), 2019)
In the development of computer network technology in society, it can help someone communicate very quickly, in terms of exchanging and sharing much of the information needed. Cacti is a graphical solution for a complete network where Cacti is designed to utilize the RRDTool power over data storage using a display in graphical form. It is intuitive and easy to use, very reliable for small LAN installations to complex networks with hundreds of devices [2]. Network monitoring activities are one of the activities carried out in processing network systems in certain areas with certain topologies. This monitoring system is used to facilitate monitoring [1]. Regarding the monitoring of the STMIK MURA campus, a monitoring technology is needed so that the networking system can be monitored optimally